Research Progress on Metabolic Regulation of Lysosomes and Their Regulatory Mechanism on Meat Tenderness - DONG Yushan, DU Rui, SU Rina, YAO Lili, DU Xuerong, LI Chenlong, WU Junqin, HOU Yanru, LUO Yulong (Shipin Kexue)
Tenderness is one of the most important indicators to judge meat quality, and it is also the most important sensory index for consumers to choose meat. Postmortem muscle undergoes complex biochemical processes, and apoptosis is considered to be a key biochemical pathway to regulate postmortem muscle tenderization. Lysosomes are rich in cathepsins, and a large amount of cathepsins are released after lysosomal membrane permeabilization, which activates the caspase cascade through the intrinsic lysosomal-mitochondrial pathway, triggering apoptosis and consequently accelerating postmortem muscle tenderization. This article introduces the action mechanism and metabolic processes of lysosomes and elaborates the activation pathways of lysosomal membrane permeabilization through reactive oxygen species (ROS), sphingosine, B-cell lymphoma-2 (Bcl-2) and p53 proteins. Furthermore, it explores the pathway for the involvement of lysosomes in apoptosis, and summarizes the regulatory mechanism of lysosomes on muscle tenderization from the perspectives of the release of cathepsins and Ca2+, caspase activation and iron-induced oxidative stress. We hope that this review can provide a theoretical reference for improving meat tenderness.